Pushing cavity-based single photon sources to the limit: photon feedback, coherent repumping and multilayer cavities - Álvarez Velásquez, JR (2022)
This thesis presents important aspects and limitations of an a priori deterministic single-photon source using single 87 Rb atoms coupled to a high finesse optical cavity. The photons emitted from this source demonstrate long coherence times, interfering over a time of up to 450 ns, demonstrating a two-photon Hong-Ou-Mandel visibility of 0.78 +/- 0.04 over the entire photon interaction time, with no degradation of coherence observed when implementing a feedback mechanism to route the photons through a desired output port.